Advance on establishment of pathological model of ulcerative colitis - Yang, Lan; Gao, Han; Liu, Dacheng (Frontiers in Veterinary Science, 2025)
Inflammatory bowel disease (IBD), comprising Crohn’s disease (CD) and ulcerative colitis (UC), is a chronic, relapsing inflammatory disorder of the gastrointestinal tract with multifactorial etiology. The etiology and pathogenesis of ulcerative colitis are diverse, so it is crucial to explore the pathogenesis through animal models. Selecting appropriate animal models is critical for advancing our understanding of UC pathogenesis and therapeutic strategies. This review discusses various UC animal models and compares their characteristics in relation to disease mechanisms and therapeutic research.